Analisis Kesalahan Ejaan pada Karangan Teks Deskripsi Siswa Kelas IX SMP Negeri 4 Padang Panjang - Khaulah Izzahti; Afnita Afnita (Journal on Education, 2025)
This study was conducted with the aim of analyzing spelling errors in descriptive texts of grade IX students of SMP Negeri 4 Padang Panjang. Writing using correct spelling is very important because it is related to the clarity of information to be conveyed in formal situations. Without understanding the use of correct spelling, students will have difficulty doing things related to writing in the future. This study used a qualitative descriptive method with data sources of 22 descriptive texts of students' works. Data were analyzed based on errors in capital letters, prepositions, pronouns, punctuation, standard words, and foreign languages. The results of this study indicate that there are 141 spelling errors consisting of 35 capital letter errors, 31 errors in affixes, prepositions, and pronouns, 62 punctuation errors, and 13 errors in standard words and foreign languages. These errors are caused by students' lack of understanding of correct spelling rules and lack of attention from teachers in the learning process. This study is expected to be able to contribute to learning to write and use correct spelling in high school students.